2021
DOI: 10.1080/1351847x.2021.1958890
|View full text |Cite
|
Sign up to set email alerts
|

Short-sale deregulation and corporate tax aggressiveness: evidence from the Chinese market

Abstract: We study whether short selling affects corporate tax aggressiveness. Exploiting staggered short-sale deregulation in the Chinese stock market as a source of variation in market pressure and monitoring, our difference-in-differences estimates show that the introduction of a shortselling scheme significantly discourages pilot firms from engaging in aggressive tax avoidance, in contrast to the findings by Luo et al. (2020). We also find that the negative effect of short selling on tax aggressiveness is more prono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…The test results showed a significant negative relationship between CEO duality and tax aggressiveness in all industries. These findings did not support Cao et al (2021) and Ezejiofor and Ezenwafor (2021). However, these findings agreed with Chytis et al (2020) and Kolias and Koumanakos (2022), which argued that it would be easier to determine company policy if the CEO also served as the board chairman.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The test results showed a significant negative relationship between CEO duality and tax aggressiveness in all industries. These findings did not support Cao et al (2021) and Ezejiofor and Ezenwafor (2021). However, these findings agreed with Chytis et al (2020) and Kolias and Koumanakos (2022), which argued that it would be easier to determine company policy if the CEO also served as the board chairman.…”
Section: Discussionmentioning
confidence: 74%
“…Meanwhile, Kashanipour et al (2019), Niu et al (2021), and Onyali and Okafor (2018) asserted that companies with a larger percentage of independent directors are less likely to engage in tax aggressiveness. Because the public considers independent boards as specialists capable of mediating conflicts amongst internal managers about decision-making, having a larger number of them enables the control role to be more successful, and the fourth hypothesis is as follows: H4: Independent board has a negative relationship with tax aggressiveness Cao et al (2021) and Ezejiofor and Ezenwafor (2021) showed a significant and positive association between CEO duality and tax aggressiveness since CEO duality increases board-management interaction. As a result, an aggressive tax policy can be promptly accepted and implemented.…”
Section: Corporate Governance Mechanismsmentioning
confidence: 99%
“…The link between CSR expenditure and tax avoidance has generated scholarly interest and debate. Some argue that firms engaged in CSR activities may be more adept at navigating tax regulations, utilising legal avenues to minimise tax liability (Choi et al, 2017). Conversely, ethical constraints imposed by CSR practices might deter firms from engaging in aggressive tax planning, suggesting a potential negative relationship.…”
Section: Introductionmentioning
confidence: 99%